1,3-Dipolar cycloaddition reaction of D-glucose-derived nitrone with allyl alcohol: synthesis of 2-hydroxy-1-deoxycastanospermine analogues - Karanjule, Narayan S.; Markad, Shankar D.; Sharma, T.; Sabharwal, Sushma G.; Puranik, Vedavati G.; Dhavale, Dilip D. (Journal of Organic Chemistry, 2005)
The synthesis and evaluation of glycosidase inhibitory activity of polyhydroxylated indolizidine alkaloids namely 2-hydroxy-1-deoxycastanospermine 3a,b and 2-hydroxy-1-deoxy-8a-epi-castanospermine 3c,d is reported. The key step involves the intermolecular 1,3-dipolar cycloaddition of allyl alcohol to D-glucose-derived nitrone 4, followed by tosylation, that afforded four diastereomeric sugar-substituted isoxazolidines 5a-d with the desired regioselectivity. The one-pot conversion of 5a-d to pyrrolidines 8a-d by hydrogenolysis, removal of 1,2-acetonoide functionality, and hydrogenation afforded corresponding target molecules 3a-d.

Aziridine carboxylate from D-glucose: synthesis of polyhydroxylated piperidine, pyrrolidine alkaloids and study of their glycosidase inhibition - Dhavale, Dilip D.; Kumar, K. S. A.; Chaudhari, Vinod D.; Sharma, T.; Sabharwal, Sushma G.; PrakashaReddy, J. (Organic & Biomolecular Chemistry, 2005)
The D-glucose derived aziridine carboxylate 5 was obtained from (E)-ethyl-6-bromo-1,2-O-isopropylidene-3-O-benzyl-5-deoxy-alpha-D-xylo-5 -eno-heptofuranuronate 4 through conjugate addition of benzylamine and in situ intramolecular nucleophilic expulsion of bromine. The regioselective aziridine ring-opening, using water as a nucleophile, resulted in the alpha-hydroxy-beta-aminoester 6, which was exploited in the synthesis of six and five membered azasugars 1b/1c and 2b/2c, respectively The glycosidase inhibitory activity of the title compounds was evaluated.

Rh(II)-catalyzed intramolecular N-H insertion of D-glucose-derived delta-amino alpha-diazo beta-ketoester: Synthesis of pyrrolidine iminosugars - Vyavahare, Vinod P.; Chattopadhyay, Subrata; Puranik, Vedavati G.; Dhavale, Dilip D. (Synlett, 2007)
The rhodium acetate catalyzed reaction of D-glucose-derived delta-amino alpha-diazo beta-ketoester allows a stereoselective beta-facial intramolecular N-H insertion reaction that leads to formation of the bicyclic pyrrolidinone ring skeleton in high yield. The sugar-substituted pyrrolidinone thus obtained was elaborated to allow the synthesis of promising glycosidase inhibitors, namely, 2,5-dideoxy2,5-imino-L-glycero-alpha-D-galactoheptitol and 2,5-dideoxy-2,5-imino-D-galactitol.
Keywords: alkaloids; azasugars; carbohydrates; N-H insertion; Pyrrolidines; rhodium carbenoid

Synthesis and glycosidase inhibitory studies of pentahydroxyindolizidines: D-Glucose-Derived aziridine-2-carboxylate approach - Kumar, K. S. Ajish; Chaudhari, Vinod D.; Puranik, Vedavati G.; Dhavale, Dilip D. (European Journal of Organic Chemistry, 2007)
D-Glucose -derived aziridine-2-carboxylate I was converted into a-amino aldehyde 7, which, after Wittig olefination, asymmetric dihydroxylation, hydrogenation followed by LiAlH4 reduction, and N-Cbz protection, afforded two diastereomeric pyrrolidines 11a and 11b with sugar appendages. Removal of the 1,2-acetonide functionality in 11a/11b and reductive animation gave the pentahydroxyindolizidine alkaloids 6g and 6h, respectively, with (S) absolute configurations at the ring junctions. The glycosidase inhibitory activities of these compounds were studied.
Keywords: asymmetric dihydroxylation (AD); Iminosugars; indolizidine; N-methylmorpholine; N-oxide (NNIO)

Synthesis of 1-deoxy-1-hydroxymethyl- and 1-deoxy-1-epi-hydroxymethyl castanospermine as new potential immunomodulating agents - Vyavahare, Vinod P.; Chakraborty, Chaitali; Maity, Biswanath; Chattopadhyay, Subrata; Puranik, Vedavati G.; Dhavale, Dilip D. (Journal of Medicinal Chemsitry, 2007)
Two new C-1 epimeric hydroxymethyl castanospermine congeners 2a and 2b, synthesized by stereocon trolled intramolecular double reductive amination Of D-glucose derived beta-keto ester as a key step, showed impressive immuno-potentiating property. The bioactivity was mediated through up-regulation of T-H1/T-H2 cytokine ratio. The finding suggested that immunmodulatory activity of polyhydroxylated indolizidine alkaloids can be tuned by minor structural/stereochemical alterations.

Synthesis of five and six membered aminocyclitols: stereoselective michael and henry reaction approach with D-glucose derived alpha,beta-unsaturated ester - Chakraborty, Chaitali; Vyavahare, Vinod P.; Puranik, Vedavati G.; Dhavale, Dilip D. (Tetrahedron, 2008)
The stereoselective intermolecular Michael addition of nitromethane to D-glucose derived alpha,beta-unSaturated ester 7 afforded L-ido-configurated nitroester 8 as the only product that on reduction of the ester functionality, cleavage of 1,2-acetonide and the intramolecular Henry reaction afforded exclusively muco-nitroinositol 9. While reduction of the ester functionality in 8, deprotection of 1,2-acetonide, oxidative cleavage with NaIO(4) and the intrarnolecular Henry reaction afforded nitrocyclopentitol 13. Nitrocyclitols 9 and 13 were converted to the hydroxyethyl substituted aminocyclohexitol 5 and aminocyclopentitol 6, respectively. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: aminocyclitols; carbohydrates; Henry reaction; Michael addition; nitroinositol

Highly diastereoselective 1,3-dipolar cycloaddition of a D-galactose-derived nitrone with dimethyl maleate: synthesis of polyhydroxylated perhydroazaazulenes - Bande, Omprakash P.; Jadhav, Vrushali H.; Puranik, Vedavati G.; Dhavale, Dilip D. (Synlett, 2009)
An intermolecular 1,3-dipolar cycloaddition of a D-galactose-derived nitrone with dimethyl maleate was found to be perfectly diastereoselective at the nitrone carbon to give exclusive formation of isoxazolidine. The N-O bond reductive cleavage in isoxazolidine followed by lactam reduction afforded a pyrrolidine ring skeleton with sugar appendage that on acetonide cleavage and reductive amino-cyclization gave hitherto unknown hydroxymethyl-substituted hexa- and pentahydroxy perhydroazaazulenes.
Keywords: 1; 3-dipolar nitrone olefin cycloaddition (DNOC); diastereoselectivity; Iminosugars; inhibitors; nitrone

Stereo-controlled approach to pyrrolidine iminosugar C-glycosides and 1,4-dideoxy-1,4-imino-L-allitol using a D-mannose-derived cyclic nitrone - Bande, Omprakash P.; Jadhav, Vrushali H.; Puranik, Vedavati G.; Dhavale, Dilip D.; Lombardo, Marco (Tetrahedron Letters, 2009)
Intramolecular N-alkylation of 2,3-O-isopropylidene-5-O-methanesulfonyl-6-O-t-butyldimethylsilyl-D-mann ofuranose-oxime 7 afforded a five-membered cyclic nitrone 9, which on N-O bond reductive cleavage followed by deprotection of -OTBS and acetonide functionalities gave 1,4-dideoxy-1,4-imino-L-allitol (DIA) 3. Addition of allylmagnesium chloride to nitrone 9 afforded alpha-allylated product 10a in high diastereoselectivity providing an easy entry to N-hydroxy-C1-alpha-allyl-substituted pyrrolidine iminosugar 4a after removal of protecting group, while N-O bond reductive cleavage in 10a afforded C1-alpha-allyl-pyrrolidine iminosugar 4b. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Cyclic nitrone; Enzyme inhibitors; Iminosugars; pyrrolidine

Synthesis and conformational study of chiral oxepines: the baylis-hillman reaction and RCM approach with sugar aldehyde - Jadhav, Vrushali H.; Bande, Omprakash P.; Pinjari, Rahul V.; Gejji, Shridhar P.; Puranik, Vedavati G.; Dhavale, Dilip D. (Journal of Organic Chemistry, 2009)
The Baylis-Hillman reaction of 3-O-allyl-alpha-D-xylo-pentodialdo-1,4-furanose 3 afforded a diastereomeric mixture of D-gluco- and L-ido-configured alpha-methylene-beta-hydroxy esters 4a and 4b, respectively, in a ratio of 2:3. Reduction of the ester functionality in 4a/4b gave alcohols 5a/5b. The diene thus formed in 5a/5b was subjected to ring-closing metathesis (Grubbs' second-generation catalyst) to afford oxa-bicyclic ring system 6a/6b in high yield. Further manipulation of the aectonide functionality in 6a and 6b afforded new polyhydroxylated oxepines 1a/2a and 1b/2b, respectively. The (1)H NMR of oxepines 1a and 1b in D(2)O showed doubling of signals indicating their existence in two different rotamers/conformers. This fact was substantiated by calculating energetics of 1 and 2 conformers using the density functional theory and correlating the calculated (1)H NMR chemical shift pattern with that of the experimental spectra.

Enantio- and diastereocontrolled total synthesis of (+)-strictifolione - Kumar, Pradeep; Pandey, Menaka; Gupta, Priti; Naidu, S. Vasudeva; Dhavale, Dilip D. (European Journal of Organic Chemistry, 2010)
A concise and practical enantioselective synthesis of (+)-strictifolione has been achieved in high diastereomeric excess using Jacobsen's hydrolytic kinetic resolution, proline-catalyzed sequential alpha-aminoxylation and Horner-Wadsworth-Emmons olefination of aldehyde and cross olefin/ring-closing metathesis as the key steps.
Keywords: Asymmetric synthesis; Hydrolytic kinetic resolution; lactones; Natural products; organocatalysis; Ring-closing metathesis; Total synthesis

Organocatalytic route to the synthesis of lactone moiety of compactin and mevinolin - Kumar, Pradeep; Pandey, Menaka; Gupta, Priti; Dhavale, Dilip D. (Tetrahedron Letters, 2010)
An efficient synthesis of lactone moiety of compactin has been achieved. The stereogenic centers were generated by means of iterative proline-catalyzed sequential alpha-aminoxylation and Horner-Wadsworth-Emmons (HWE) olefination of aldehydes. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Aminoxylation; Compactin; Lactone; organocatalysis; Proline

Synthesis of azepane and nojirimycin iminosugars: the sharpless asymmetric epoxidation of D-glucose-derived allyl alcohol and highly regioselective epoxide ring opening using sodium azide - Jadhav, Vrushali H.; Bande, Omprakash P.; Puranik, Vedavati G.; Dhavale, Dilip D. (Tetrahedron-Asymmetry, 2010)
The Sharp less asymmetric epoxidation of D-glucose-derived ally! alcohol 4 afforded alpha- and beta-epoxides 5a and 5b in high stereoselectivity. The epoxide ring opening in 5a/5b was studied with different nucleophilic azido reagents, under various reaction conditions, and was found to be highly regioselective to give the preferential formation of 6-azido diol 6a/6b over 5-azido-diol 7a/7b. The 6-azido diol 6a/6b and 5-azido dial 7a/7b thus obtained were converted to the corresponding seven- and six-membered iminosugar, namely, azepane 1a/1b and 1-deoxy-nojirimycin 2a/2b. (C) 2010 Elsevier Ltd. All rights reserved.

Synthesis of eight-membered iminocyclitols from D-glucose - Jadhav, Vrushali H.; Bande, Omprakash P.; Puranik, Vedavati G.; Dhavale, Dilip D. (Tetrahedron, 2010)
The Baylis-Hillman reaction of 3-o-benzyl-alpha-d-xylo-pentodialdo-1,4-furanose 2 afforded a diastereomeric mixture of L-ido- and D-gluco-configurated alpha-methylene-beta-hydroxy esters 3a and 3b, respectively, in 1:1 ratio. Conjugate addition of benzyl amine on 3a gave adduct 4a as a major product while, addition of benzyl amine to 3b gave only one diastereomer 4b. Reduction of ester functionality in 4a/4b, opening of 1,2-acetonide functionality followed by reductive amino-cyclization under hydrogenation condition afforded azocanes 1c/1d in good yield. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Baylis-Hillman reaction; Conjugate addition; diastereoselectivity; Iminosugars

Synthesis of C1- and C8a-epimers of (+)-castanospermine from D-glucose derived gamma,delta-epoxyazide: intramolecular 5-endo epoxide opening approach - Kalamkar, Navnath B.; Puranik, Vedavati G.; Dhavale, Dilip D. (Tetrahedron, 2011)
A concise synthesis of two diastereomers of (+)-castanospermine namely 1- and 8a-epi-castanospermine 1b and 1c, respectively, is reported from D-glucose. The methodology involves stereoselective cross metathesis of D-glucose derived alkene 2 with 4-bromo-1-butene followed by azide displacement and m-CPBA oxidation to afford diastereomeric gamma,delta-epoxyazides 5a/5b. The Staudinger reaction of epoxyazide 5a followed by reaction with benzylchloroformate (CbzCl) unexpectedly furnished 1,3-oxazinan-2-one derivative 7 whose stereochemistry was establish by single crystal X-ray. This helps to assign the stereochemistry in the epoxidation reaction. The reduction of 5a/5b was then carried out by transfer hydrogenation to provide gamma,delta-epoxyamine that concomitantly undergoes intramolecular 5-endo-tet cyclization to afford hydroxypyrrolidine ring skeleton with sugar framework-a precursor to castanospermine analogues 1b/1c. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: alkaloids; Cross metathesis; D-Glucose; Epoxide; Oxazinanone; Polyhydroxy indolizidines

Alpha-geminal dihydroxymethyl piperidine and pyrrolidine iminosugars: synthesis, conformational analysis, glycosidase inhibitory activity, and molecular docking studies - Pawar, Nitin J.; Parihar, Vijay Singh; Chavan, Sanjay T.; Joshi, Rakesh S.; Joshi, Pranaya V.; Sabharwal, Sushma G.; Puranik, Vedavati G.; Dhavale, Dilip D. (Journal of Organic Chemistry, 2012)
The Jocic-Reeve and Corey-Link type reaction of dichloromethyllithium with suitably protected 5-keto-hexofuranoses followed by treatment with sodium azide and sodium borohydride reduction gave 5-azido-5-hydroxylmethyl substituted hexofuranoses 7a-c with required geminal dihydroxymethyl group. Removal of protecting groups and converting the C-1 anomeric carbon into free hemiacetal followed by intramolecular reductive aminocyclization with in situ generated C5-amino functionality afforded corresponding 5C-dihydroxymethyl piperidine iminosugars 2a-c. Alternatively, removal of protecting groups in 7b and 7c and chopping of C1-anomeric carbon gave C2-aldehyde that on intramolecular reductive aminocyclization with CS-amino gave 4C-dihydroxyrnethyl pyrrolidine iminosugars 1b and 1c, respectively. On the basis of the H-1 NMR studies, the conformations of 2a/2b were assigned as C-4(1) and that of 2c as C-1(4). The glycosidase inhibitory activities of all five iminosugars were studied with various glycosidase enzymes and compared with natural o-g/uco-l-deoxynojirimycin (DNJ). All the five compounds were found to be potent inhibitors of rice alpha-glucosidase with K-i and IC50 values in the nanomolar concentration range. Iminosugars 2b and 1b were found to be more potent inhibitors than their parent iminosugar. These results were substantiated by in silico molecular docking studies.

Organocatalytic stereoselective synthesis of passifloricin A - Kumar, Pradeep; Pandey, Menaka; Gupta, Priti; Dhavale, Dilip D. (Organic & Biomolecular Chemistry, 2012)
The enantioselective synthesis of passifloricin A has been achieved in high diastereomeric excess. The 1,3-polyol moiety was constructed by iterative proline-catalyzed sequential alpha-aminoxylation and Horner-Wadsworth-Emmons (HWE) olefination of aldehydes while the synthesis of lactone moiety was achieved by ring-closing metathesis (RCM).

Sugar furanoid trans-vicinal diacid as a gamma-turn inducer: synthesis and conformational study - Vangala, Madhuri; Dhokale, Snehal A.; Gawade, Rupesh L.; Pattuparambil, Rajamohanan R.; Puranik, Vedavati G.; Dhavale, Dilip D. (Organic & Biomolecular Chemistry, 2013)
A simple method for the synthesis of a sugar furanoid trans vicinal diacid and its incorporation into the N-terminal tetrapeptide sequence (H-Phe-Trp-Lys-Thr-OH) to get glycopeptide 8 has been described. 2D NMR and MD simulation studies of 8 clearly show that the sugar diacid adopts a gamma-turn conformation towards the N-terminus.

Self-assembly of fluorinated sugar amino acid derived alpha,gamma-cyclic peptides into transmembrane anion transport - Burade, Sachin S.; Saha, Tanmoy; Bhuma, Naresh; Kumbhar, Navanath; Kotmale, Amol; Rajamohanan, Pattuparambil R.; Gonnade, Rajesh G.; Talukdar, Pinaki; Dhavale, Dilip D. (Organic Letters, 2017)
Syntheses of fluorinated sugar amino acid derived alpha,gamma-cyclic tetra- and hexapeptides are reported. The IR, NMR, ESI-MS, CD, and molecular modeling studies of cyclic tetra- and hexapeptides showed C-2 and C-3 symmetric flat oval- and triangular-ring shaped, beta-strand conformations, respectively, which appear to self assemble into nanotubes. The alpha,gamma-cyclic hexapeptide (EC50 = 2.14 mu M) is found to be a more efficient ion transporter than alpha,gamma-cyclic tetrapeptide (EC50 = 14.75 mu M). The anion selectivity and recognition of alpha,gamma-cyclic hexapeptide with NO3- ion is investigated.

Retraction: organocatalytic stereoselective synthesis of passifloricin A (Retraction of Vol 10, Pg 1820, 2012) - Kumar, Pradeep; Pandey, Menaka; Gupta, Priti; Dhavale, Dilip D. (Organic & Biomolecular Chemistry, 2019)